Kriging method for missing rainfall data - 493687 Liaw, Pei Chin; Ani Shabri; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2008